A SURVEY ON WORKING ENVIRONMENT AND PROBLEMS OF THE MAIZE VENDORS - D. RATNA KUMARI, DEEPIKA PANDEY and (The Journal of Research, PJTSAU, 2019)
In many cities and towns of developing countries, street food vending is a large source of employment (Choudhury et al., 2011) and contributessignificantly to household incomes (Biswas et al., 2010). Roasted maize cob (Bhutta) is classic Indian street food that would be found generally at the beginning of the rainy season or the monsoons. Roasting of maize is done by placing it on a glowing charcoal and then turning it occasionally to allow even distribution of heat. Various indigenous  roasting equipments are used by vendors for roasting purposes like tandoor, barbecue, grill, corn roaster etc. A hand fan is used by the vendor to blow the air so as to maintain the glowing of charcoal. The rate of heat transfer from the charcoal to the maize depends on how fast the hand fan blows the air current. For constant supply of air; hand fan and blower are preferred. In the models of stoves used by the local street vendors only two or three corns can be roasted at a time. When the number of customers is more, it becomes difficult for the vendor to cater to all at the same time. There are a number of problems being faced by the road side vendors. Despite problems and risks associated with the business, people continue to use this as a source of earning their living (Pearce and Bankole, 1988).